The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11738-008-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent impact of 24-epibrassinolide on the fatty acid composition and sugar content in winter oilseed rape callus

Abstract: The aim of this experiment was to study the effect of 24-epibrassinolide (BR 27 ) on fatty acids composition and sugar content in winter oilseed rape callus cultured at 20 and 5°C. Studies have showed that BR 27 action is highly temperature-dependent. The increase in sugar content (sucrose, glucose and fructose) by BR 27 in concentration 100 nM was observed only in calli cultured at 20°C. At 5°C, quite the opposite effect of BR 27 action was observed; where cold increased the sugar content, BR 27 decreased it.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…In agriculture, the potential of brassinosteroids application is based on their ability to increase yield of crops (Khripach et al 2000). They have also the capability to protect plants from various environmental stresses such as drought, extreme temperatures, heavy metals, herbicidal injury, and salinity (Bhardwaj et al 2006, Hayat et al 2010c, Janeczko et al 2008. The present study showed that both the brassinolides tested stimulated plant growth.…”
Section: Discussionmentioning
confidence: 55%
“…In agriculture, the potential of brassinosteroids application is based on their ability to increase yield of crops (Khripach et al 2000). They have also the capability to protect plants from various environmental stresses such as drought, extreme temperatures, heavy metals, herbicidal injury, and salinity (Bhardwaj et al 2006, Hayat et al 2010c, Janeczko et al 2008. The present study showed that both the brassinolides tested stimulated plant growth.…”
Section: Discussionmentioning
confidence: 55%
“…The potential applications of brassinosteroids in agriculture are based on their ability to increase crop yields (Khripach et al, 2000). Brassinosteroids also have strong potential to protect plants from various environmental stresses, including drought, extreme temperatures, heavy metals, herbicidal injury and salinity (Bhardwaj et al, 2006;Krishana, 2003;Haubrick and Assmann, 2006;Janeczko et al, 2008). Present study showed that under field conditions when temperature conditions were favorable with high day temperature (25 ºC±2 ºC) and low night temperature (18 ºC±2 ºC), both brassinolides stimulated germination and seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…In plants subjected to stress conditions, BRs affect (positively or negatively) the activity of antioxidant enzymes, synthesis of various osmoprotectants, synthesis of heat shock proteins, the fatty acid composition of membrane lipids, etc. (Ali et al , 2008aArora et al 2008;Hayat et al 2007;Janeczko et al 2009;Kartal et al 2009;Mazorra et al 2002;Ö zdemir et al 2004;Shahbaz et al 2008;Singh and Shono 2005). Photosynthesis, transpiration and nitrogen fixation in plants are also influenced by BRs (Ali et al 2008b;Fariduddin et al 2003;Farooq et al 2009;Hayat et al 2000;Li et al 2008;Sairam 1994a, b;Swamy and Rao 2008;Yu et al 2004), as well as the distribution of assimilates to various plant organs (Fujii and Saka 2001).…”
Section: Introductionmentioning
confidence: 99%